(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Psoriasis is a common chronic, immune-mediated, inflammatory, proliferative, non-contagious disease of the skin affecting people who are genetically predisposed, with environment playing a critical role in the pathogenesis. There is no satisfactory treatment available in contemporary science as the recurrence rate is high, but Ayurved treatment can give promising result in such patients. Here in this case a 65 yrs old female came to OPD with complaints of cracks with intermittent bleeding in bilateral feet, thickened erythematous plaque, itching at the site of the lesion intense pain at the affected site, along with blackish discolouration of the bilateral feet. Looking into the Samprapti (pathogenesis) of the disease it Vata kapha pradhana tridosaja vikara, then the patient is administered with Kaishora gugulu and Maha manjisthadi Kashaya for internal medication along with Jeevantyadi yamak as external application. Within 1 month of treatment patient get satisfactory relieve in sign and symptoms.